2023
DOI: 10.1002/rcs.2518
|View full text |Cite
|
Sign up to set email alerts
|

The learning curve for a novel, fluoroscopy‐based robotic‐assisted total hip arthroplasty system

Abstract: Background Adoption of robotic‐assisted total hip arthroplasty (RA‐THA) systems can improve the accuracy of acetabular cup placement, but no group has reported the learning curve of novel, fluoroscopy‐based RA‐THA systems. Methods A learning‐curve cumulative summation (LC‐CUSUM) analysis was performed on a consecutive series of the first 100 patients who received fluoroscopy‐based RA‐THA by the study surgeon. Operative times and specific robotic timepoints were compared between learning and proficiency phases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Fourth, as the RA-THA cohort included the first fluoroscopy-based RA-THA cases performed by the study surgeon, it is possible that there was a learning curve effect for postoperative pain control. However, it has been previously reported that no learning curve effect was seen with this robotic system with respect to cup placement [ 32 ], thus it is unlikely that a learning curve exists with respect to postoperative pain control.…”
Section: Discussionmentioning
confidence: 95%
“…Fourth, as the RA-THA cohort included the first fluoroscopy-based RA-THA cases performed by the study surgeon, it is possible that there was a learning curve effect for postoperative pain control. However, it has been previously reported that no learning curve effect was seen with this robotic system with respect to cup placement [ 32 ], thus it is unlikely that a learning curve exists with respect to postoperative pain control.…”
Section: Discussionmentioning
confidence: 95%
“…The second signi cant nding of this study was that the FL-RTHA and CT-RTHA platforms had similar accuracy outcomes, and also had similar proportions of cups placed within the Lewinnek zone. The authors surmise that the observed 1.2° difference in inclination accuracy between systems is a result of the FL-RTHA cohort including cases from the surgeon's learning period with the system, which is traditionally associated with inferior surgical performance compared to the post-pro ciency stage [32,33]. One investigation reported an average cup implantation angle difference of 2.8° for inclination, and 3.5° for anteversion between pre-and post-pro ciency procedures when adopting an intra-operative assistance system for THA [34].…”
Section: Discussionmentioning
confidence: 99%
“…Racial minorities historically experience diminished pre-and post-operative PROMs relative to Caucasians, [39][40][41][42] and patients with a pre-operative diagnosis of avascular necrosis may report inferior pain outcomes following THA compared with patients with osteoarthritis. 43 Additionally, unlike the CT-RTHA cohort, the FL-RTHA cohort included cases performed during the surgeon's learning period for the robot, 44 which could have resulted in inferior outcomes relative to cases performed post-proficiency. 45 The learning period is likely an important driving factor for the 1.06°d ifference in inclination accuracy observed between the FL-RTHA and CT-RTHA cohorts.…”
Section: Discussionmentioning
confidence: 99%